1998
DOI: 10.1002/(sici)1097-0290(19980705)59:1<52::aid-bit7>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of denitritification and denitratification in anoxic filters

Abstract: Denitritification and denitratification in anoxic filters were performed to generate experimental data. Also, a kinetic model of denitratification that accounts for intrinsic biokinetics and hydrodynamic behavior of the biofilter is proposed. In denitritification, the simulated results are in good agreement with the experimental data; and a higher nitrite influent concentration gives a higher nitrite reduction efficiency if the denitrifying loading is kept the same. In denitratification, the intermediate nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…8). The values of the biofilm thickness were very close to those presented by Huang et al ,2 who indicated that the biofilm thickness can be varied between 1244 and 614 µm. The profile of the biofilm thickness throughout the reactor agrees with those found by several authors 24, 30–32.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…8). The values of the biofilm thickness were very close to those presented by Huang et al ,2 who indicated that the biofilm thickness can be varied between 1244 and 614 µm. The profile of the biofilm thickness throughout the reactor agrees with those found by several authors 24, 30–32.…”
Section: Resultssupporting
confidence: 87%
“…These results indicate that the DM process in biofilm tubular reactors is affected principally by mass transfer in the biofilm and not by nitrogen compound inhibition of methanogenesis. The mass transfer in the biofilm has been indicated as a limiting factor by several authors,2, 30, 36 and this depends on hydraulic conditions and biofilm thickness 37. Huang et al 2 indicates that the denitrification process in a biofilter can be considered as having a deep‐biofilm kinetics for biofilm thickness as high as 540 µm, and therefore, the mass transfer resistance in the biofilm should not be neglected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…nitrite reduction to gaseous N 2 ). Furthermore, nitrate and nitrite have been found to inhibit denitrification systems [1,[7][8][9][10][11][12]. Although detailed information is provided in the literature for the inhibition on each individual denitrification step, little attention has been paid to the possible inhibitory effect of sound inhibitor-nitrite with pH considered as a very important factor on denitrification.…”
Section: Introductionmentioning
confidence: 99%